Invasion genetics of the yellow-legged hornet Vespa velutina in the Westernmost Mediterranean archipelago - Cayetano Herrera; Joana F. Ferragut; Mar Leza; José Antonio Jurado-Rivera (Journal of Pest Science, 2024)
The yellow-legged hornet ( Vespa velutina ) is a social Hymenoptera native from Asia and an invasive species in Europe, where it was first detected in France in 2004. Since then, the species has spread across the continent invading mainland Spain and Mallorca island (Balearic archipelago, Western Mediterranean) in 2010 and 2015, respectively. Yellow-legged hornets cause severe damage to ecosystem by predating over a wide variety of pollinators including honeybees. Such a threat situation requires the development of effective management and prevention plans, which can greatly benefit from knowing both the origin and the genetic structure of the invading populations. Here we conduct a genetic study to shed light on both the origin and the phylogenetic relationships of V. velutina populations from Mallorca and mainland Spain using nuclear (STRs) and mitochondrial (cytochrome oxidase c subunit 1) gene markers. Our results show that Mallorca populations originated from invasive European specimens. Moreover, FST values, DAPC and genetic structure analysis suggest two independent incursions in the island with bottleneck and founder effect signatures. Finally, we contribute additional genetic evidence of the polyandrous behavior of this invasive species based on the inference of a mean number of mattings per nest of 3.94 (range 2–6.5). This study supports the human-mediated pathways of this species and highlights the importance of implementing effective biosecurity measures to prevent the spread of invasive alien species in island habitats.

First genetic survey on the invasive rayed pearl oyster Pinctada radiata (Leach, 1814) populations of the Balearic Islands (Western Mediterranean) - JOSEBA AGUILO-ARCE; JOANA FERRAGUT F.; LYDIA PNG-GONZALEZ; AINA CARBONELL; MARÍA CAPA (Mediterranean Marine Science, 2023)
A survey of the invasive pearl oyster Pinctada radiata along the Balearic Archipelago was conducted based on the COI mitochondrial marker. Results confirmed the identity of the specimens as P. radiata. The Balearic populations are certainly of Indo-Pacific origin but not from the Persian Gulf nor from other introduced populations in the eastern or central Mediterranean, therefore the precise origin remains to be discovered. Despite the small number of samples from the Persian Gulf compared to the Mediterranean, the haplotype diversity is higher in the native populations compared to the non-native.

Persimmon orchards harbor an abundant and well-established predatory mite fauna - F. Omar García-Martínez; Alberto Urbaneja; Francisco Ferragut; Francisco J. Beitia; Meritxell Pérez-Hedo (Experimental and Applied Acarology, 2019)

Reproductive performance of seven strains of the tomato red spider mite Tetranychus evansi (Acari: Tetranychidae) at five temperatures - T. Gotoh; N. Sugimoto; A. Pallini; M. Knapp; E. Hernandez-Suarez; F. Ferragut; C.-C. Ho; A. Migeon; M. Navajas; G. Nachman (Experimental and Applied Acarology, 2010)

Feeding behavior ofEuseius stipulatus andTyphlodromus phialatus on the citrus red mitePanonychus citri [Acari: Phytoseiidae, Tetranychidae] - F. Ferragut; R. Laborda; J. Costa-Comelles; F. García-Marí (BioControl, 1992)